Combination targeted therapy of VEGFR inhibitor, sorafenib, with an mTOR inhibitor, sirolimus induced a remakable response of rapid progressive Uterine PEComa. Issue 6 (2nd June 2016) - Gao, Fang; Huang, Chengsuo; Zhang, Yiping; Sun, Ruirui; Zhang, Yujie; Wang, Huijun; Zhang, Shu
ABSTRACT: Perivascular epithelioid cell tumor is a rare tumor. To date, there is no consensus of therapy to be recommended for unresectable disease. For a low incidence and a rarely curable disease, the finding of new therapy is essential. Here we report the first case of a patient with perivascular epithelioid cell tumor whose disease had a rapid progression after surgery and had a rapid remarkable response of combination therapy of a VEGFR inhibitor, sorafenib, with an mTOR inhibitor, sirolimus. This result may have potential to deliver a new treatment option and inhibiting the mTOR pathway combined with inhibiting the VEGF pathways may be a useful strategy for malignant PEComas.